KONSEP HASAD DALAM PERSPEKTIF NĀṢIR MAKĀRIM ASH-SHĪRĀZĪ: Studi Atas Kitab Al-Akhlāq Fī Al-Qur’ān - Nur Khanifah; Endang Sri Rahayu (LPPM STAI Nida El-Adabi, 2025)
Hasad is the desire for the happiness that others possess to be taken away from them. A person with hasad does not like to see others living better or happier than themselves. In Islamic history, the impact of hasad is evident in the story of Habil and Qabil. In the social context, particularly in Indonesia, many conflicts, such as murders, enmities, and hatred, are largely driven by hasad. Approximately 80% of these cases are motivated by envy, resentment, and bitterness. Therefore, the Qur'an also addresses hasad, though scholars (mufassir) have diverse interpretations of it. This study aims to discuss and analyze the verses of the Qur'an related to hasad through a social approach, specifically from the perspective of Nāṣir Makārim ash-Shīrāzī in his book Al-Akhlāq fī Al-Qur’ān. This research employs a thematic method and a qualitative approach. The results show that the concept of hasad in the Qur'an, according to Nāṣir Makārim ash-Shīrāzī, views hasad as a reprehensible trait that leads to deviant behavior, such as weakening of faith and greed. Hasad is the desire to take away others' blessings, arising from arrogance, love of the world, hostility, and stinginess. It triggers social conflicts and negatively affects individual and communal life. The cure for hasad involves knowledge and action, replacing negative behaviors with positive ones. Makārim ash-Shīrāzī emphasizes the importance of loving goodness for others as a part of Islamic ethics.